2011
DOI: 10.1088/1741-2560/8/5/056008
|View full text |Cite
|
Sign up to set email alerts
|

Optical validation ofin vitroextra-cellular neuronal recordings

Abstract: Simultaneous calcium imaging and extra-cellular recordings from cultured cortical rat neurons were performed to directly map the efficacy of extra-cellular recordings with microelectrodes. For the first time, we can associate extra-cellular recordings with neuronal activity of specific neurons in the vicinity of the electrode. We demonstrate that recorded cells can be identified by correlating the electrical signals and the calcium response. Our data demonstrate that in sparse cultures, microelectrodes record … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Imaging and electrophysiological studies have shown that (because of low impedance of the medium surrounding the neurons) the electrodes of the MEA can only capture activity of neurons that lie in very close vicinity to the electrodes (e.g., Herzog et al 2011). We have observed the same phenomena by patch-clamping single cells at Conditions 1-8 denote the drugs that were applied and (consequently) the receptors that remained functional.…”
Section: Cross-correlationmentioning
confidence: 53%
“…Imaging and electrophysiological studies have shown that (because of low impedance of the medium surrounding the neurons) the electrodes of the MEA can only capture activity of neurons that lie in very close vicinity to the electrodes (e.g., Herzog et al 2011). We have observed the same phenomena by patch-clamping single cells at Conditions 1-8 denote the drugs that were applied and (consequently) the receptors that remained functional.…”
Section: Cross-correlationmentioning
confidence: 53%
“…5(d), the suppression level increased monotonically as the pattern size increased. Considering that an electrode captures neural activity from cells within close distance (60 μm) [27], adjusting the diameter of circular illumination pattern might be controlling the number of neurons that influence the recording neuron. The inhibition was also dependent upon the distance from the illumination area, which made it possible to obtain area-specific neural inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures were prepared as described in Herzog et al (2011). After the fourth day in vitro , the growth medium was enriched with 0.5% Pen-Strep (Biological Industries Beit Haemek), 2% B-27 (Gibco), and 0.75% glutamax (Biological Industries Beit Haemek).…”
Section: Methodsmentioning
confidence: 99%